Technical challenges in 3 T magnetic resonance spectroscopic imaging of the prostate—A single-institution experience - Choi, Haesun (AME Publishing Company, 2014)
The magnetic resonance spectroscopic imaging (MRSI) is the only technique that is currently available in the clinical practice to provide the metabolic status of prostate tissue at the cellular level with a great potential to improve the clinical patient care. Increasing the field strength from 1.5 to 3 T can theoretically provide proportionately higher signal-to-noise ratio (SNR) and improve spectral separation between prostatic metabolite peaks. The technique, however, has been limited to a few academic institutions that are equipped with a team of experts primarily due to due to serious technical challenges in optimizing the spectral quality. High quality shimming is key to the successful MRSI acquisition. Without optimization of the increased field inhomogeneity and radiofrequency (RF) dielectric effect at 3 T, the spectral peak broadening and residual signal from the periprostatic fat tissue may render the overall spectra non-diagnostic. The purpose of this technical note is to present the practical steps of successful acquisition of 3 T MRSI and to address several important technical challenges in minimizing the effect of the increased magnetic field and RF field inhomogeneity in order to obtain highest possible spectral quality based on our initial experience in using 3 T MRSI prototype software.